Measurement report: Closure analysis of aerosol–cloud composition in tropical maritime warm convection - E. Crosbie; E. Crosbie; L. D. Ziemba; M. A. Shook; C. E. Robinson; C. E. Robinson; C. E. Robinson; E. L. Winstead; E. L. Winstead; K. L. Thornhill; K. L. Thornhill; R. A. Braun; et al. (Atmospheric Chemistry and Physics, 2022)
Cloud droplet chemical composition is a key observable property that can aid understanding of how aerosols and clouds interact. As part of the Clouds, Aerosols and Monsoon Processes – Philippines Experiment (CAMP2Ex), three case studies were analyzed involving collocated airborne sampling of relevant clear and cloudy air masses associated with maritime warm convection. Two of the cases represented a polluted marine background, with signatures of transported East Asian regional pollution, aged over water for several days, while the third case comprised a major smoke transport event from Kalimantan fires.